Efficacy of combined phage-gentamicin therapy for the control of antibiotic-resistant Staphylococcus aureus - Karn, Subhash Lal; Sahu, Minakshi; Myneedu , Vitthal Prasad; Nath, Gopal (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Biofilm is a leading cause of antibiotic resistance and chronic infections. Studies have shown that microbial biofilms are 100–10,000 times more resilient to antimicrobial substances. Several studies have demonstrated the efficacy of bacteriophage-antibiotic combinations in planktonic cultures of S. aureus. This study was undertaken to evaluate the efficacy of phage-antibiotic combinations in eradicating Staphylococcus aureus biofilms.Methods: The study evaluated the combined treatment of phage and antibiotic at a specific dose, order, and timing, yielding the most effective killing outcome compared with treatment with either one alone. Results: The present study demonstrated the superior effectiveness of the phage-antibiotic combination compared to phage-only or antibiotic-only treatments. Combination therapy outperformed mono-treatments. The combined bactericidal effect of the antibiotic and phage is more pronounced in the Phage First (PF) treatment. Sequential treatment, involving phage application before eight hours of antibiotic exposure at a concentration of 108 PFU/mL, proved the most efficient in eradicating both biofilms and the planktonic form of S. aureus.Conclusion: The synergistic effect of phages and antibiotics on biofilm eradication was observed, and the combination proved beneficial for treating bacteria in the biofilm matrix. Phage-antibiotic synergism offers a promising avenue for developing antibiotic-phage combinations that meet therapeutic requirements for treating S. aureus infections. The results of this study offer fresh insights into phage therapy.